Does Social Media Content Affect Purchase Intention in Indonesia's Apparel Industry? - Prasetyaningtyas, Sekar Wulan; Komajaya, Eka Putera; Soesilo, Theresia (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2022)
Changes in people's behavior are impacting the increase of social media users, especially Instagram. As a visual-based social media, Instagram provides several opportunities for business owners to reach and build relationships with their target consumers through social media content. This study aims to determine the effectiveness of content shown on social media Instagram to customer engagement and purchase intention in the apparel industry in Indonesia's Jabodetabek area. This study uses a Uses and Gratification Theory (UGT) approach to explain people's motivation in using social media. The data collection method in this study uses an online questionnaire distributed to 127 active Instagram users aged 18-34 years who have seen the content of apparel products. The data analysis method in this study uses the PLS-SEM method through Smart PLS 3 software. This study result shows that the remunerative content and relational content of apparel products affect customer engagement. Moreover, customer engagement also affects the purchase intentions of apparel products. However, the vividness of content, informational content, and entertaining content of apparel products do not affect customer engagement.